Estudo de caso com uma rede reduzida em baixa tensão, a dois condutores, alimentando cargas trifásicas indutivas e resistivas - Rabelo, Selso (2021)
The importance and growth of agrobusiness in Brazil and the world requires the energetic sector to develop in such a way that it can keep up with and support the demand for electrical energy by eficient and economic means to the field producers. There are many forms to effectively distribute energy in the countryside. However, there is also the need to ally efficiency and quality to low cost supply. To achieve this goal, for long there have been researches in order to find solutions that could fit the necessities of those who live and produce in the rural area, in particular those who reside at great distances from urban centers. Initially, monophasic systems were capable of complying with such necessities through systems as the Monophasic with Neuter Return (MNR) and also the Monophasic with Ground Return (MGR). With the advent of industrial revolutions, wich have approximated the agrobusiness to the machines and modern equipments, there came into being the necessity of enhancing the supply of energy at the field, with the increase of phases in the electrical grid, especially the three-phase grid. Extending a three-phase grid for long distances implies a high installation cost and, to reduce these costs, occur innovative proposes that ally efficiency and low cost at triphasic tension distibution. The purpose of this paper is precisely to present how to distribute triphasic tension to long distances, in rural areas, for example, so that the expense of the distribution becomes way inferior than a conventional three-phase three wired grid. The paper proposes a study of the conduction of electricity through the ground, in other words, for the triphasic distribution in the countryside to be, the already existing two overground phases are employed so that the 3o phase is conducted through the soil. With emphasis on the 3° phase grounding system, the proposal is developed with the mounting of a low tension (LV) reduced electrical grid, so that it supplies a few equilibrated triphasic loads. There are made measurements of the grounding in order to verify its level of influence on the conduction of the ground current. At the end, the results obtained from the measurements in the practical mounting are compared to the simulated results, verifying that the system is totally viable.